THE CASE OF KAPOSI’S SARCOMA AMONG ELDERLY WOMEN - D. V. Zaslavsky; S. V. Skrek; A. V. Sobolev; A. A. Sidikov; A. A. Yunovidova; P. Wolkenstein; А. V. Truntova; L. R. Сhernova (Журнал инфектологии, 2016)
The article presents an analysis of a clinical  case of a patient  of 76 years, describes the key links  in the pathogenesis of Kaposi’s  sarcoma  virus,  and  the  modern concept of participation in the pathogenesis of the disease. A feature of this clinical  observation was the  development of the  disease on the background of the functional immunosuppression, which developed because of old age. Besides the standard protocol of conducting a similar  profile  of patients therapy led to the development of side  effects. In turn,  the optimization of the therapeutic protocol  has  allowed to avoid  side  effects from the  treatment, continue therapy led  to  complete convalescence.